HUBUNGAN PENGETAHUAN DENGAN PERILAKU PENCEGAHAN HIV/AIDS PADA MAHASISWA TINGKAT IV PROGRAM STUDI X FAKULTAS X UNIVERSITAS X TAHUN 2023 - Santoso S. Kep., Ners M. Kep, Mochamad Budi; Novilla, Arina; Mulyono, Ilham; Juhaeriah, Juju; Kamdah, Musri (JURNAL KESEHATAN KARTIKA, 2024)
T Background: The high rate of HIV/AIDS cases in late adulthood needs to be anticipated with prevention at an earlier age, namely in late adolescence to reduce the incidence of HIV/AIDS in late adulthood and late adolescence. Objective: This research was conducted with the aim of knowing the relationship between knowledge and HIV/AIDS prevention behavior in students. Method: The Cross-sectional analytic survey design used a total sampling technique with a total sample of 146 respondents.  Collecting data using a questionnaire with primary data taken directly from the respondents. Univariate and bivariate analyses were performed using the Chi-square test. Results: The results showed that 102 out of 122 (83.6%) respondents had good knowledge and good behavior. While 11 out of 24 (45.8%) respondents had less knowledge and less behavior. The results of the Chi-Square test showed that there was a relationship between knowledge and HIV/AIDS prevention behavior with a P value of 0.003 <0.05. ConclusionThe conclusion of this study is that there is a relationship between Knowledge and HIV/AIDS Prevention Behavior in students. Suggestions for institutions, It is hoped that they can make routine policies/programs regarding fostering sex education, oblige students to take part in student activities, and conduct screening for HIV/AIDS